Maternity protection policies and the enabling environment for breastfeeding in the Philippines: a qualitative study - Cherry C. Maramag; Jyn Allec R. Samaniego; Mary Christine Castro; Paul Zambrano; Tuan T Nguyen; Jennifer Cashin; Janice Datu-Sanguyo; Roger Mathisen; Amy Weissman (BMC, 2023)
Abstract Background The Philippines has enacted maternity protection policies, such as the 105-Day Expanded Maternity Leave Law and the Expanded Breastfeeding Promotion Act of 2009, to protect, promote, and support breastfeeding. This study aimed to review the content and implementation of maternity protection policies in the Philippines and assess their role in enabling recommended breastfeeding practices. It also identified bottlenecks to successful implementation from the perspectives of mothers and their partners, employers, and authorities from the government and non-government organizations involved in developing, implementing, monitoring, and enforcing maternity protection policies. Methods This study employed a desk review of policies, guidelines, and related documents on maternity protection, and in-depth interviews. Of the 87 in-depth interviews, there were 12 employed pregnant women, 29 mothers of infants, 15 partners of the mothers, 12 employers and 19 key informants from the government and non-government organizations. Respondents for the in-depth interviews were from the Greater Manila Area and were recruited using purposive snowball sampling. Data were collected from December 2020 to April 2021. Results The study shows that maternity protection policies in the Philippines are mostly aligned with the maternity protection standards set by the International Labour Organization. However, their role in improving breastfeeding practices is limited because: (1) not all working women have access to maternity protection entitlements; (2) the duration of maternity leave entitlements is inconsistent with the World Health Organization's recommended duration of exclusive breastfeeding; (3) there are gaps in policy implementation including: a lack of monitoring systems to measure the availability, functionality, and usage of lactation spaces; limited workplace support for breastfeeding; poor communication of maternity and paternity entitlements; and limited breastfeeding advocacy and promotion; and (4) there is limited integration between maternity protection and breastfeeding promotion interventions. Conclusions There is a need to (1) strengthen communication about and promotion of maternity and paternity entitlements for mothers, fathers and employers, (2) improve monitoring and enforcement mechanisms to ensure utilization of entitlements among mothers, (3) develop modalities to extend the coverage of maternity entitlements to the informal sector, (4) fully cover paid leave entitlements from social insurance or public funding sources in line with International Labour Organization recommendations, and (5) revisit the limitations on the coverage of paternity entitlement.